Balcony on the upper floor of the Matha - Temples of India Project Team (Jio Institute, 2024)
The upper floor of the matha (monastic or residential) in the Suhaveshwar temple complex has a balcony that is right above the mukhamandapa (front porch) on the ground floor. This balcony is made up of four pillars that support a flat ceiling. The base of the balcony has an opening that leads to a small room. The layout and style of this balcony is similar to the transepts in the mandapas (pillared halls) of the Suhaveshwar and Mahanaleshwar temples.